Worldwide Research Trends on Smart Homes - Salmerón-Manzano, Esther; Rahmani-Andebili, M.; Alcayde, Alfredo; Manzano-Agugliaro, Francisco (Springer Science and Business Media Deutschland GmbH, 2022)
Research in smart homes is still quite recent; however, there is no doubt that it will become a pervasive research topic in the near future. This chapter analyzes the whole research production on smart homes indexed in the Scopus database from 1985 to 2019, yielding a total of 11,000 studies. One of the goals of this chapter is to identify the main countries and institutions that have published on this topic and what their interest has been throughout the time. Four out of 116 countries stand out in this field, namely China, USA, India, and South Korea. In terms of the main institutions, the three with the highest scientific output are Ulster University (UK), CNRS Centre National de la Recherche Scientifique (France), and Universite Grenoble Alpes (France). Another aim of the chapter is to determine the research fields and subfields investigated about smart homes. The publications are mainly focused on two scientific fields, that is, computer science and engineering, accounting for 64% of the overall scientific production. In an aggregate analysis of all publications, four main clusters have been identified, namely Internet of Things, Activity Recognition, Security, and Energy.
Keywords: automation; intelligent buildings; smart home; internet of things (IoT); domestic appliances; energy utilization; ubiquitous computing; artificial intelligence; smart power grids; energy management; sensors; wireless sensor networks; energy efficiency; Scopus(2)